Cost-effectiveness of scaling up of hepatitis C screening and treatment: a modelling study in South Korea. Issue 3 (4th June 2019) - Kim, Jungyeon; Haacker, Markus; Keshavjee, Salmaan; Atun, Rifat
Abstract : Background: The prices and the coverage of effective direct-acting antivirals (DAAs) to treat hepatitis C vary across countries. South Korea expanded DAAs coverage through national health insurance. This study aims to analyse the cost-effectiveness of scale-up of hepatitis C screening and treatment with DAAs in South Korea, a high-income country. Methods: This study uses a compartmental age–sex structured model of progression of hepatitis C to analyse effects of different policy choices for the scale up of screening and treatment with DAAs on hepatitis C disease burden and costs from 2017 to 2050. Policy scenarios considered in our study are (1) no treatment, (2) status quo, (3) screening population aged over 60 years, (4) screening population over 40 years and (5) screening population aged over 20 years. Results: The continuation of current policy with the expansion of DAAs coverage is estimated to reduce the prevalence of hepatitis C antibody from 0.6% in 2015 to 0.25% in 2050 of the adult population. Status quo policy, screening from age 60, screening from age 40 and screening from age 20 are cost-effective in terms of averted infection at estimated incremental cost-effective ratio of US101 208, US111 770, US107 909 and US229 604. Conclusions: The expansion of DAAs coverage by the national health insurance is highly effective in alleviating hepatitis C disease burden. The scale-up of screening and treatment with DAAs for targeted adult population with high prevalence of hepatitis C is cost-effective. This study provides a case for policy-makers to invest in rapid expansion of hepatitis C comprehensive screening and treatment with DAAs.